Cirugía con manga gástrica en paciente de 24 años, reporte de caso: Gastric sleeve surgery in a 24-year-old patient, case report - Verdugo-Tapia, Juan Carlos (2023)
Abstrac: Obesity is a global health problem affecting 1.5 billion adults worldwide, including children and adolescents, resulting in increased physical and mental health issues. Obese individuals are at higher risk of developing metabolic and cardiovascular diseases, as well as malignant tumors, resulting in higher mortality rates. Laparoscopic sleeve gastrectomy is widely used in bariatric surgery to reduce mortality. Although sleeve gastrectomy induces anatomical changes and weight loss, there is still a lack of long-term evidence on its effectiveness. A clinical case of a patient with grade II obesity is shared. Keywords: Body mass index, gastrectomy, gastric bypass, obesity.